A Dendritic Nanostructured Copper Oxide Electrocatalyst for the Oxygen Evolution Reaction. (4th April 2017) - Huan, Tran Ngoc; Rousse, Gwenaëlle; Zanna, Sandrine; Lucas, Ivan T.; Xu, Xiangzhen; Menguy, Nicolas; Mougel, Victor; Fontecave, Marc
Abstract: To use water as the source of electrons for proton or CO2 reduction within electrocatalytic devices, catalysts are required for facilitating the proton‐coupled multi‐electron oxygen evolution reaction (OER, 2 H2 O→O2 +4 H + +4 e − ). These catalysts, ideally based on cheap and earth abundant metals, have to display high activity at low overpotential and good stability and selectivity. While numerous examples of Co, Mn, and Ni catalysts were recently reported for water oxidation, only few examples were reported using copper, despite promising efficiencies. A rationally designed nanostructured copper/copper oxide electrocatalyst for OER is presented. This material derives from conductive copper foam passivated by a copper oxide layer and further nanostructured by electrodeposition of CuO nanoparticles. The generated electrodes are highly efficient for catalyzing selective water oxidation to dioxygen with an overpotential of 290 mV at 10 mA cm −2 in 1 m NaOH solution.